2022
DOI: 10.3390/jcm11247374
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Visual Outcome Analysis of a Diffractive Multifocal Intraocular Lens and a New Diffractive Multifocal Lens with Extended Depth of Focus

Abstract: This study compares the visual and refractive performance of the TECNIS Synergy (DFR00V-DFW150-225-300-375) multifocal intraocular lens (IOL) and the AcrySof IQ PanOptix (TFAT00-30-40-50-60) multifocal IOL. Patients who underwent phacoemulsification and cataract extraction and received either a multifocal Synergy or PanOptix IOL were included. Monocular uncorrected distance (UDVA), intermediate (UIVA), near (UNVA), and corrected distance (CDVA) visual acuities were assessed at three and six months postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 60 publications
3
20
1
Order By: Relevance
“…However, as with every trifocal IOL, halos and glare persist at night. [15][16][17][18]31,32 The near and intermediate vision achieved using the ZFR00V IOL is excellent. The combination of enhanced monofocal lenses with such performances could lead to higher patient satisfaction, as determined by Labiris et al, who combined a monofocal IOL and trifocal IOL to yield better outcomes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, as with every trifocal IOL, halos and glare persist at night. [15][16][17][18]31,32 The near and intermediate vision achieved using the ZFR00V IOL is excellent. The combination of enhanced monofocal lenses with such performances could lead to higher patient satisfaction, as determined by Labiris et al, who combined a monofocal IOL and trifocal IOL to yield better outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…This design element splits incoming light, generating intermediate and near-addition powers. [15][16][17][18] Surgical Procedure All the procedures were consistently conducted by the same experienced surgeon, following standard protocols. Phacoemulsification was performed through a temporal clear corneal incision, and a foldable posterior chamber IOL (ZRF00V or ICB00) was inserted into the capsular bag.…”
Section: Study Iolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synergy, a newer mixed EDOF and multifocal IOL, has been shown to deliver a high level of spectacle independence at near, intermediate, and distance. There is even some evidence showing that the Synergy may deliver better near visual acuity and mesopic contrast sensitivity compared to the PanOptix, which may improve patient satisfaction amongst myopes and patients who desire stronger near vision [ 35 ]. Few myopes were included in this study, but one patients with baseline myopia did report lower satisfaction due to the inability to see fine print up close postoperatively, while all other myopes reported good or very good satisfaction with the PanOptix IOL.…”
Section: Discussionmentioning
confidence: 99%
“…EDOF designs have generally been associated with decreased photic effects compared to trifocal designs [29][30][31], though some meta-analyses found that the incidence of halos is the same for EDOF compared with trifocal [32] or that there is insufficient information to compare the two IOLs [33]. 'Mix-andmatch' bifocal IOL implantation seems to also be superior to EDOF in terms of visual disturbances [34].…”
Section: Complicationsmentioning
confidence: 99%